Diseño de planta de lavado por hidrociclón para el área secundaria del Quebrador Ochomogo Ltda. - Manosalva-Serrano, Milena Andrea (Instituto Tecnológico de Costa Rica, 2018)
This project will be developed at Quebrador Ochomogo Ltda. It is located near Llano Grande,Cartago. The company produces aggregates for construction, moreover focused on increasing of their competitiveness. Also, they can offer a product who is made based to the client nessecities. The crusher it’s posed the design of a hydrociclon washing plant, in the second plant of the crusher. For the developement of this project it is necessary to divide in into four sections; the hydrociclon structure, hydrociclon, the pipe for the transporting of material to the thickener tank and vibrating screen. Every one of this section will be apportioned, with the objective of complete the design of the plant as a whole. For the structure design we are considering the best way to develop the maintenance at the hydrociclon, because it suffer a constant high wearing, it is very important the frequent revision of each parto of the hydrociclon, for their respective replacement; specially the replacement of the nozzle, that suffer a high wearing. Finally, we restored an unesed vibrating screen to reduce material and implementation cost and take advantage of existing resources.
Proyecto Final de Graduación (Licenciatura en Ingeniería en Mantenimiento Industrial) Instituto Tecnológico de Costa Rica, Escuela de Ingeniería Electromecánica, 2018.
Keywords: Piedra; Trituración; Arena; Research Subject Categories::TECHNOLOGY::Engineering mechanics